2022
DOI: 10.31557/apjcp.2022.23.2.743
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxic and Anti-Migratory Properties of Caesalpinia sappan and Ficus septica, in Combination with Doxorubicin on 4T1 TNBC Cells with Nephroprotective Potential

Abstract: Objective: To evaluate the anti-cancer properties of Caesalpinia sappan and Ficus septica in combination with doxorubicin on 4T1 cells, confirm their nephroprotective activities, and predict the molecular targets of the underlying mechanisms. Methods: The cytotoxic activities of all extracts and doxorubicin were determined by MTT assay followed by cell cycle and apoptosis analysis using flow cytometry. Immunoblotting was used to determine the protein expressions. The proteins involved in the cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…When combined with chemotherapeutic drugs such as Paclitaxel and Vemurafenib, Navitoclax, a Bcl-2 inhibitor, increases cell Metastasis involves some mechanisms in cancer cells, starting from extracellular matrix disruption by the family of MMPs, cell adhesion, and invasion of a cancer cell on the other tissues, which mainly correlated with cell migration. (19,20) This process continued until the cell reached the second host tissue and completed the metastasis process. (20,31,32) However, extracellular matrix disruption in cancer was regulated by MMP-9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When combined with chemotherapeutic drugs such as Paclitaxel and Vemurafenib, Navitoclax, a Bcl-2 inhibitor, increases cell Metastasis involves some mechanisms in cancer cells, starting from extracellular matrix disruption by the family of MMPs, cell adhesion, and invasion of a cancer cell on the other tissues, which mainly correlated with cell migration. (19,20) This process continued until the cell reached the second host tissue and completed the metastasis process. (20,31,32) However, extracellular matrix disruption in cancer was regulated by MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…(1,3) Using these characteristics as the basis, we explored the potential influence of the CEO on TNBC senescence and cell migration. Our research group reported that sappan wood extract (CSE) decreases cell senescence and inhibits TNBC cancer cell line migration (17,19), manifested by the main contents in sappan wood ethanolic extract, brazilin, and brazilein (20,21). Meanwhile, the activity of CEO on the TNBC cell line, including its senescence induction or metastasis inhibition activity, has yet to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…An in silico study predicted several targets that brazilin inhibited. In triple breast cancer, brazilin was found to attach more firmly and effectively to MMP-2, MMP-9, and PTGS2 compared to its native ligand (Haryanti et al, 2022). These enzymes are involved in cell migration and metastasis (Webb et al, 2017;Ercolano et al, 2019).…”
Section: Brazilin Mechanisms In Cancermentioning
confidence: 99%
“…The cytotoxic evaluation was conducted based on the metabolically active cells to convert 3-(4,5-dimethylthiazol2-yl)-2,5-diphenyltetrazolium bromide (MTT) into an oxidative form of formazan that can be detected using visible light (Haryanti et al 2022). The cytotoxic test of the Ethyl Acetate Fraction of Melinjo Seeds (EAFMS) on HeLa cancer cells was carried out by inserting cells with a density of 300 cells/6,700 µl MK into 96 well plates of 100 µl each and providing 3 empty wells to be used as controls, then incubated for 48 hours at 37°C.…”
Section: Cytotoxic Activity Using Mtt Assaymentioning
confidence: 99%
“…According to Haryanti et al (2022), after incubation, discharging the medium, and washing with PBS (Sigma), each well received 0.5 mg/ml MTT (Sigma) in the medium and was incubated for 3-4 h, followed by adding 10% SDS in 0.01 N HCl and incubated overnight without light. Then viewed under an inverted microscope, purple formazan crystals formed, indicating that the surviving cells react with MTT.…”
Section: Cytotoxic Activity Using Mtt Assaymentioning
confidence: 99%